Development of dimethyl ether synthesis processes using by-product gas from a steel-making plant: Single-vs. two-step processes - Park, Hyeon; Woo, Yesol; Jung, Hyun Seung; Kim, Gookhee; Bae, Jong Wook; Park, Myung June (Journal of Cleaner Production, 2021)
This work addresses the development of a DME synthesis process from a mixture of coke oven gas (COG) and FINEX tail gas (FTG) from a steel-making plant. Two different syngas-to-DME processes were considered: one using two separate reactors for the methanol synthesis over Cu–ZnO–Al2O3 (CZA) and the methanol dehydration over ferrierite (FER) zeolite catalysts, and the other using a single reactor by physically mixing the two catalysts. Kinetic models were developed for each catalyst and the kinetic parameters were estimated by fitting the experimental data at various conditions of temperatures, pressures, space velocities, and feed compositions. The process modeling results showed that the single reactor achieved a CO conversion of 88.1% and a DME production rate of 450 kg/h, while the corresponding values for the method employing two separate reactors were 38.6% and 240 kg/h, respectively. This difference is attributable to the spontaneous conversion of the produced MeOH to DME, by the coexistence of the two catalysts, which shifted the equilibrium of MeOH production forward. The comparison between the open-loop and recycled cases showed that the carbon efficiency could be more than doubled for both reactor configurations when the unreacted gas was recycled. Finally, the single-reactor configuration employing the recycled stream produced DME at a rate of 825.9 kg/h with the complete consumption of CO and a CO2 conversion of 76%. This indicated that such a process would maximize the use of by-product gas and increase the economic feasibility of steel-making plants.
Keywords: By-product gas; Dimethyl ether production; Kinetic models; Physical mixing; Process-models; Product gas; Single reactor; Single-step; Single-step reactor; Steel making; By-product gas; Dimethyl ether production; Kinetic model; Physical mixing; Process modeling; Single-step reactor